Russian and Ukrainian perspectives on the concept of information confrontation translations, 2002-2020 - Grisé, Michelle (RAND Corporation, 2022)
In this volume, the authors of several translated articles, which were published between 2002 and 2020, provide insight into the evolution of military-scientific thinking in both Russia and Ukraine on the concept of information confrontation. The authors detail the impact of the rapid development of information technologies and information weapons over the past two decades on the military-scientific literature of Russia and Ukraine. The articles in this volume provide insight into the varying definitions and subtypes of information confrontation, its historical evolution and application, the technical tools used in the conduct of information confrontation, and the relationship between the connected yet distinct concepts of information confrontation and information warfare
Keywords: Geschichte 2002-2020; Information warfare; Russland; Ukraine; Information warfare / Russia (Federation); Information warfare / Ukraine; Psychological warfare / Russia (Federation); Psychological warfare / Ukraine; Russia (Federation) / Foreign relations / Ukraine; Ukraine / Foreign relations / Russia (Federation); Quelle